Public opinion on cash transfers for children and adolescents in Colombia: Nine out of ten support expanding amounts - Blofield, Merike (2023)
Poverty is a multidimensional phenomenon and decades of evidence demonstrate that periodic cash transfer programs can provide simple and effective protection against poverty, especially extreme poverty. A nationally representative telephone survey conducted in Colombia between June and July 2022 indicates broad support among the population (92.5%) for the existence of a cash transfer program for children and adolescents. In addition, 96% support fixing the value of the transfers to at least the basic food basket. Finally, public opinion is more divided on the eligibility criteria. Slightly more than half (54%) support restricting transfers to those in extreme poverty, while 45% support broader criteria, at least for all children and adolescents in poverty.